2018
DOI: 10.4317/medoral.22019
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis and cell cycle aberrations in epithelial odontogenic lesions: An evidence by the expression of p53, Bcl-2 and Bax

Abstract: BackgroundAmeloblastoma (AMB), odontogenic keratocyst (OKC) and adenomatoid odontogenic tumor (AOT) are epithelial odontogenic lesions with diverse biologic profiles. Defects in regulation of apoptosis and cell cycle may be involved in the development and progression of those lesions, therefore we aimed to investigate the expression of Bcl-2, Bax and p53 to better understand the possible role of these proteins in AMBs, OKCs and AOTs.Material and MethodsThe studied sample consisted of 20 AMBs, 20 OKCs and 20 AO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 17 publications
0
13
0
5
Order By: Relevance
“…In a study conducted by Carvalhais and coworkers, 36 positivity for p53 was not observed in 51 cases of odontogenic cysts and tumors assessed, and even though a relationship between p53 positivity and a more aggressive behavior had been suggested, their cases of clear cell odontogenic lesions were negative for p53. In contrast, Tenório et al 37 observed that p53 protein was expressed in all cases of ameloblastomas, OKCs, and AOTs. The expression of this tumor suppression infers that there is a greater dysregulation in cell cycle control in lesions with a more aggressive biological behavior, such as ameloblastoma and OKC, reinforcing the possible neoplastic phenotype of some odontogenic lesions.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In a study conducted by Carvalhais and coworkers, 36 positivity for p53 was not observed in 51 cases of odontogenic cysts and tumors assessed, and even though a relationship between p53 positivity and a more aggressive behavior had been suggested, their cases of clear cell odontogenic lesions were negative for p53. In contrast, Tenório et al 37 observed that p53 protein was expressed in all cases of ameloblastomas, OKCs, and AOTs. The expression of this tumor suppression infers that there is a greater dysregulation in cell cycle control in lesions with a more aggressive biological behavior, such as ameloblastoma and OKC, reinforcing the possible neoplastic phenotype of some odontogenic lesions.…”
Section: Discussionmentioning
confidence: 83%
“…The expression of this tumor suppression infers that there is a greater dysregulation in cell cycle control in lesions with a more aggressive biological behavior, such as ameloblastoma and OKC, reinforcing the possible neoplastic phenotype of some odontogenic lesions. 37 In minor salivary gland intraductal MEC, no p53 overexpression was demonstrated. 38 The p63 was also positive in the case presented, in accordance with other cases of CEOTs reported elsewhere.…”
Section: Discussionmentioning
confidence: 96%
“…p53 can control the occurrence of apoptotic gene expression. On the one hand, p53 promotes the apoptotic protein expression, such as Bad, Bax, Bak, and so forth, and on the other hand, it reduces the expression of apoptotic protein [14], such as the Bcl-2, the Bcl-xl. The relative ratio of Bax/Bcl-2 determines the occurrence of apoptosis [15].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Tenorio et al . ( 23 ) and Rangiani et al . ( 25 ) reported in OKCs a low expression of Bcl-2 extended to the basal cell layer of the epithelial lining, while Bax showed a diffuse weak labeling.…”
Section: Discussionmentioning
confidence: 96%